The Majazi Polemic in the Al-Qur’an, the Relevance of the Trigger for the Birth of the Study of Balaghah Science - Sutrisno, Febby Intansari Nuraini (Maliki Interdisciplinary Journal, 2024)
The value of literary beauty contained in an expression is the spirit of the expression itself. Al-Qur’an which is the holy book of Muslims which contains the words of Allah which were revealed using Arabic is a gift to be grateful for. From its uniqueness, it was the aim of earlier scholars to study it. The Al-Qur’an which contains matters regarding monotheism, shari’at, morals and so on, of course, in conveying its meaning, the language style of the Qur’an is used which is so beautiful. As with the use of majaz in the style of language, this is a debate among scholars about its truth. The reason is that each scholar gives a different argument regarding majaz, it is said that it is just a lie, as well as the art of speaking to divert its original meaning. Of course no one blames the existence of these differences. But in essence it is impossible for Allah swt. use simple language in conveying His word. Considering that at that time the socio-cultural condition of the Arab world, its literature developed quite rapidly. Because this is what attracts the author to conduct further research to find out the truth.